Deformation-induced pearlite transformation and spheroidization of bearing steel for new energy vehicles - Zhihui Chen; Xiaolong Gan; Man Liu; Zhengliang Xue; Hao Tian; Desheng Li; Guang Xu (Journal of Materials Research and Technology)
Effects of deformation strains on the microstructure and mechanical properties of bearing steel for new energy vehicles were investigated by combining thermal simulation testing machine with optical microscopy, field-emission scanning electron microscopy, electron backscatter diffraction technology, scanning transmission electron microscopy and hardness tests, etc. The results show that the warm deformation of the undercooled austenite at temperatures close to Ar1 induced the γ-Fe to pearlite transformation. With the increase of deformation strain from 20% to 75%, the volume fraction of deformation-induced pearlite increased gradually, the spheroidization of cementite occurred, and the hardness of the tested steel decreased from 720 HV to 361 HV. When the deformation strain reached 75%, the micron ferrite grains with average size of 2.46 μm and nano-sized spherical carbides of 81 nm formed. EBSD results show that with increasing the deformation strain, the size of pearlite colony decreased, the size of pearlite nodules, and the proportion of high-angle grain boundaries decreased first and then increased. Moreover, the kinetic curve of the deformation-induced pearlite was fitted and the strengthening mechanism of the tested steel was analyzed. The theoretical calculation results of yield strength were in good agreement with the experimental data.